Emotions and crime: towards a criminology of emotions - Jacobsen, Michael Hviid; Walklate, Sandra (Routledge, 2019)
Crime and emotions -- Male violence against women in intimate relationships : the contribution of stress and male peer support / Walter S. Dekeseredy -- The role of emotions for female co-offenders / Charlotte Barlow -- American self-radicalising terrorists and conversions to radical action : emotional factors and the allure of "jihadi cool/chic" / Caroline Joan "Kay" S. Picart -- "Violence is difficult, not easy" : the emotion dynamics of mass atrocities / Susanne Karstedt -- Punishment and emotions -- "45 colour photographs" : images, emotions and the victim of domestic violence / Dawn Moore with Stephanie Lizon -- Punitiveness and the emotions of punishment : between solidarity and hostility / Anastasia Chamberlen and Henrique Carvalho -- Capital punishment and the emotional public sphere in mid-20th century Britain / Lizzie Seal -- Doing criminology as emotion work -- Prison life as "emotion culture" : reflections on some of the emotional challenges of conducting prison ethnography / Michael Hviid Jacobsen and Dorte Raaby Andersen -- Witnessing, responsibility and spectatorship in the aftermath of violence : reflections from Srebrenica / Elizabeth Cook -- Death justice : navigating contested death in the digital age / Rebecca Scott Bray -- "Feeling criminology" : learning from emotions in criminological research / Stephen Wakeman -- Postscript: concluding thoughts : some lessons from being "liminal" / Sandra Walklate -- Index.